PENINGKATAN KUALITAS PADA PENGECATAN HELM SHELL MENGGUNAKAN METODE LEAN SIX SIGMA - Ferdinand; Ahmad; Saryatmo, Mohammad Agung (Universitas Tarumanagara, 2023)
Quality improvement is always essential for companies to compete with products circulating in the market and for the development of a company. PT kandakawana Sakti is a manufacturing company engaged in painting services for shell helmet products. Based on the results of the analysis, it was obtained in the helmet painting production process that the 3 largest wastes occurred, namely waste defects, waste motion, and waste overproduction. The research was conducted using the lean six sigma method with DMAIC principles, which aims to minimize waste that occurs and increase the productivity of the company. After data processing, waste defects were obtained by 18.027%, waste motion by 18.87 and waste overproduction by 15.79%. It is obtained from the current value stream mapping that the production process has a process cycle efficiency of 26.76%. In the calculation of the DPMO value and sigma level, the DPMO value of 36,433 products with a sigma level of 3.29 was obtained. In this study, improvements were made in the form of making check sheets for maintenance tools, checking sheet mixing paint, checking sheets of scratch material materials and making one point lessons for defect dimensions, one point lesson absorb paint, and one point lesson runny paint. After the implementation of the proposed improvement, a recalculation of the DPMO value and sigma level was carried out. The DPMO value after the implementation of the improvement became 1,259 products and the sigma rate was 4.52 and there was an increase in process cyle efficiency to 33.56%.